The Strategies Used by Teachers to Teach ADHD Students at Athirah Islamic Elementary School - Syam, Adeliah Nurmuthmainnah; Dollah, Syarifuddin; Muliati, Andi (JEKPEND: Jurnal Ekonomi dan Pendidikan, 2025)
Teaching English to ADHD students is certainly not an easy task. The characteristics of ADHD students, such as being very active, having difficulty focusing, and struggling to control their emotions, present unique challenges for teachers when teaching English in the classroom. Therefore, knowledge of appropriate teaching strategies for ADHD students is essential for teachers. This thesis aims to explore the strategies used by teachers to teach English to ADHD students at Athirah Islamic Elementary School. This research design uses case study qualitative methods. The subject of this study are 3 teachers consists of main teacher and two support teachers who teach ADHD students in grade 6 of Athirah Islamic Elementary School. Data collection was conducted through non-participant observation and semi-structure interview. The results of this study reveal seven strategies employed by teachers are, structured environment, visual aids, interactive learning, immediate feedback, frequent breaks, differentiated instruction, and co-teaching. This study contributes valuable insights into effective teaching strategies for ADHD students.